Hypoxia-inducible factor in cancer - Aldecoa Bedoya, Franklin (2023)
Oxygen and carbon dioxide are essential for breathing; variations in these gases outside of the normal range are a threat to cell survival. Hypoxia is a common condition that occurs in most malignant tumors, increases angiogenesis and defective vascularization, promotes cell proliferation and acquires an epithelial–mesenchymal transition phenotype, which causes metastasis. It also affects cancer cell metabolism and makes patients resistant to treatment by causing cell quiescence. As a result, hypoxia is a detrimental component that is linked to unfavorable outcomes in most cancer treatments. Through the activation of more than a hundred genes that control cell activity, which produce key functions for cancer development, the transcription factor known as hypoxia-inducible factor (HIF) is linked to hypoxia in cancer. This review’s main goals are to highlight the role of hypoxia in the development of cancer, identify the key molecules that interact to promote HIF expression, explain the molecular mechanisms of the pathways that lead to HIF induction, describe the cellular effects of HIF alteration, and discuss potential HIF-targeted therapies. Articles from 1990 to 2022 were reviewed in PubMed, Scopus and SciELO databases. Keywords related to cancer and HIF were searched in bibliographical references. In conclusion, HIF-1α overexpression in tumor biopsies is associated with increased patient mortality in human cancers. Potential HIF-1α-regulated target genes that may play a role in tumor progression are starting to be identified. Although hundreds of chemicals have been studied in relation to HIF in cancer, there are currently few approved HIF inhibitors available on the global market; moreover, many clinical trials, in their various stages of development, do not show encouraging results. It is likely that in the future, when there is a better understanding of the structure, molecular and biological functioning of this factor, more specific drugs for HIF inhibition will be developed.